Driven-dissipative non-equilibrium Bose–Einstein condensation of less than ten photons. Issue 12 (December 2018) - Walker, Benjamin; Flatten, Lucas; Hesten, Henry; Mintert, Florian; Hunger, David; Trichet, Aurélien; Smith, Jason; Nyman, Robert
Abstract In a Bose–Einstein condensate, bosons condense in the lowest-energy mode available and exhibit high coherence. Quantum condensation is inherently a multimode phenomenon, yet understanding of the condensation transition in the macroscopic limit is hampered by the difficulty in resolving populations of individual modes and the coherences between them. Here, we report non-equilibrium Bose–Einstein condensation of 7 ± 2 photons in a sculpted dye-filled microcavity, where the extremely small particle number and large mode spacing of the condensate allow us to measure occupancies and coherences of the individual energy levels of the bosonic field. Coherence of the individual modes is found to generally increase with increasing photon number. However, at the break-down of thermal equilibrium we observe phase transitions to a multimode condensate regime wherein coherence unexpectedly decreases with increasing population, suggesting the presence of strong intermode phase or number correlations despite the absence of a direct nonlinearity. Experiments are well-matched to a detailed non-equilibrium model. We find that microlaser and Bose–Einstein statistics each describe complementary parts of our data and are limits of our model in appropriate regimes, providing elements to inform the debate on the differences between the two concepts1, 2 . Non-equilibrium Bose–Einstein condensation of 7 ± 2 photons is observed in a sculpted dye-filled microcavity. The small number of particles allows the authors to access and characterize the non-equilibrium dynamics of the bosonic modes.